2003
DOI: 10.2224/sbp.2003.31.2.107
|View full text |Cite
|
Sign up to set email alerts
|

Motivational Goal Orientations of Intellectually Gifted Achieving and Underachieving Students in the United Arab Emirates

Abstract: The purpose of this study was to investigate the differences between intellectually gifted achieving and underachieving secondary school students on certain motivational goal orientations such as effort, task, competition, power, praise, feedback, token, social concern, and social dependency. A total of 144 selected United Arab Emirates secondary school male students (15-19 years of age) participated in the investigation. Participants were classified into the following two intellectually gifted groups: achiev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 38 publications
0
14
0
6
Order By: Relevance
“…For example, successful adolescents insist more on intellectual leisure activities and academic subjects (Class 3) than the students with lower academic performance (Classes 1 and 2). The focus placed by the successful adolescents on the intellectual and academic areas could explain their high academic performance and the fact that they valued knowledge for knowledge's sake as well as all that an academic institution had to offer (e.g., Albaili, 2003). The status of good student could, in return, bring the concerned students to structure their representations of self around the intellectual and academic sphere, compared to their counterparts experiencing difficulty.…”
Section: Discussionmentioning
confidence: 99%
“…For example, successful adolescents insist more on intellectual leisure activities and academic subjects (Class 3) than the students with lower academic performance (Classes 1 and 2). The focus placed by the successful adolescents on the intellectual and academic areas could explain their high academic performance and the fact that they valued knowledge for knowledge's sake as well as all that an academic institution had to offer (e.g., Albaili, 2003). The status of good student could, in return, bring the concerned students to structure their representations of self around the intellectual and academic sphere, compared to their counterparts experiencing difficulty.…”
Section: Discussionmentioning
confidence: 99%
“…Although some work has explored relations between externalizing behavior problems and underachievement (Hinshaw, 1992), students with severe emotional problems, attention deficit disorders, and learning disabilities are typically excluded from the definition of underachievement (Albaili, 2003;Reis & McCoach, 2000). The ability-achievement gap in students with learning disabilities refers to a discrepancy between fluid ability or processing speed and performance as measured by knowledge test or standardized achievement test (Swanson, 2011), and is likely better conceptualized as an ability-learning discrepancy.…”
Section: Underachievement Vs Learning Disabilitiesmentioning
confidence: 99%
“…This aspect of underachievement has been largely overlooked in prior research. Many prior studies have examined underachievement as dichotomized ability-achievement discrepancy at a single time point (e.g., Albaili, 2003;Lau & Chan, 2001a, b;McCoach & Siegle, 2003;Rayneri, Gerber, & Wiley, 2003), and some select research has also examined predictors in degree of ability-achievement discrepancy (Preckel et al, 2006). Mean-level difference research has provided insight into potential constructs that warrant further empirical investigation, such as students' perceptions of competence and value for academics.…”
Section: Chronicity Of Underachievementmentioning
confidence: 99%
“…Payne, Rueda, and Dembo (2009) found significant differences in learning goal orientation between gifted achievers and gifted underachievers in secondary school with disadvantages for the latter group. In his discriminant analysis of goal orientations, Albaili (2003) found that learning goal orientation and competition differentiated gifted achievers and gifted underachievers in secondary school. Here as well, achievers had higher levels of learning goal orientation and were more competitive than underachievers.…”
Section: Motivation Among Gifted Underachieversmentioning
confidence: 99%